A Study of Palladium-Nickel Catalyst for Direct Synthesis of Hydrogen Peroxide: A DFT Approach - Mawan Nugraha; Susiani Pupon; Nofiandri Setyasmara (JPSE (Journal of Physical Science and Engineering), 2020)
Hydrogen peroxide is an important material for bleaching agent in paper production related to the low price and environmentally friendly chemical. The current production of H2O2 is well-known as indirect synthesis, which uses danger anthraquinone. The synthesis was improved by using the direct reaction of H2 and O2 on Pd or PdAu alloy's catalyst surface and has been known as direct synthesis. The current catalyst used is Pd-Au, but it has limited availability in nature. Therefore we need the alternative of Pd-Au. We investigated Ni alloyed with Pd for the new H2O2 direct synthesis catalyst using a density functional theory approach. We selected the O adsorption to screen the catalysts and compared the species adsorption trend on the surfaces of PdNi and the proven catalysts such as Pd, PdAu, and PdHg. Since the trend of O adsorption on the PdAu and PdNi is similar, it can be concluded that the catalytic selectivity of PdNi equal with PdAu. Further, the stability of PdNi alloy was explored by calculating the binding and compared it with Pd, which leads to the conclusion that PdNi can be a good catalyst for H2O2 synthesis.DOI: http://dx.doi.org/10.17977/um024v5i22020p046